ANALISIS STRATEGI PENINGKATAN PENDAPATAN TABUNGAN HAJI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAYTUL IHKTIAR CABANG LEUWISADENG, KABUPATEN BOGOR, JAWA BARAT - Putra, Gilang Permana; Thantawi, Tubagus Rifqy; Mursyidah, Azizah (SAHID BANKING JOURNAL, 2024)
This research aims to analyze and find out the current internal and external environment of KSPPS Baytul Ihktiar Leuwisadeng Branch, especially with regard to community empowerment through Hajj Savings at KSPPS Baytul Ihktiar Leuwisadeng Branch, analyze and find out what factors are internally and externally attached to KSPPS Baytul Ihktiar Leuwisadeng Branch in community empowerment through Hajj Savings, as well as analyzing and knowing the strategies that need to be carried out by KSPPS Baytul Ihktiar Leuwisadeng Branch in empowering the community through Hajj Savings. The method used is a qualitative method, with SWOT analysis techniques. The results of the study stated that based on the IFAS and EFAS matrix tables with a total value of IFAS 2.40 and EFAS 3.11. The next strategy that must be carried out by KSPPS Baytul Ihktiar Leuwisadeng Branch in developing the Islamic economy and empowering the community through Hajj Savings is to concentrate on Vertical Integration, which is a strategy that aims to further strengthen the market share of Hajj Savings by expanding the network in Bogor Regency and its surroundings.